Nonsteroidal Anti-Inflammatory Drugs (NSAIDs): Progress in Small Molecule Drug Development - Praveen P. N. Rao; Saad N. Kabir; Tarek Mohamed (Pharmaceuticals, 2010)
Ever since the discovery of aspirin, small molecule therapeutics have been widely prescribed to treat inflammation and pain. Aspirin and several small molecule NSAIDs are known to inhibit the enzymes cyclooxygenase-1 (COX-1) and -2 (COX-2). Despite the success of NSAIDs to treat inflammatory disorders, the development of a clinically useful small molecule NSAIDs with decreased side effect profiles is an ongoing effort. The recent discovery and development of selective COX-2 inhibitors was a step toward this direction. Emerging trends are represented by the progress in the development of hybrid agents such as nitric oxide donor-NSAIDs (NO-NSAIDs) and dual COX/lipoxygenase (LOX) inhibitors. This review focuses on the recent advances in the rational design of small molecule NSAIDs in therapy.